Infections caused by halophilic marine Vibrio bacteria. - Howard, R J (1993)
OBJECTIVE: The authors reviewed patients who developed sepsis or soft tissue infections caused by marine Vibrio bacteria in Florida. SUMMARY BACKGROUND DATA: Marine Vibrio bacteria are the most common bacteria found in seawater. They are concentrated in marine animals that feed by filtration such as oysters and clams. These bacteria can cause gastroenteritis, sepsis, cellulitis leading to necrotizing soft tissue infection after exposure to seawater or consumption of raw seafood. METHODS: The authors received 182 systemic infections that occurred in Florida between January 1, 1979, and December 31, 1991, which were treated by the authors or were reported to the Florida Department of Health and Rehabilitative Services. Patients were divided into two groups depending on whether they presented with primary bacteremia or soft tissue infection. RESULTS: Seventy-one patients had been exposed to these bacteria by eating raw seafood, 94 had direct exposure to seawater, and exposure was uncertain in 27 patients. Vibrio species were cultured from the blood of 103 patients and from wounds or soft tissues of 113. An additional 5 patients had cellulitis but bacteria were not cultured from these sites. In patients in whom it could be determined, 93 had primary soft tissue infections and 82 had primary bacteremia. Twenty-four patients had necrotizing soft tissue infections and required surgical debridement. Three of these 24 patients required amputation. Thirty-seven (20.3%) patients died. Severe liver disease occurred in 54 patients and 25 of these patients died. CONCLUSIONS: Marine Vibrio bacteria can cause sepsis and soft tissue infections, especially in individuals with severe liver disease and other chronic illnesses such as diabetes mellitus. The authors believe all individuals, especially those with systemic illness, should be warned against eating raw seafood.